Effects on abstinence of nicotine patch treatment prior to quitting smoking: a parallel, two-arm, pragmatic randomised trial - Aveyard, Paul; Lewis, Sarah; Coleman, Tim; Dickinson, Anne; Randall, Clare; Orton, Sophie; Perdue, Jo (BMJ Publishing Group, 2018)
Objectives: Standard smoking cessation pharmacotherapy is recommended in the post-quit period, but may also facilitate abstinence if used prior to quitting. The objective was to examine the effectiveness and cost-effectiveness of nicotine patch worn for four weeks before a quit attempt.